ANALYSIS OF FACTORS AFFECTING THE DEMAND FOR MORTGAGE CREDIT IN PT. X - Dairatil Irvan, Syamsu; Nusraningrum, Dewi (Dinasti International Journal of Management Science, 2021)
PT X is a financial institution that distributes credit, one of which is mortgage credit or home ownership credit (KPR). The realization of mortgage lending at PT X from 2017 to 2020 has not been able to reach the target due to lack of credit demand. This study analyzes the interest rate, service, procedure, term, guarantee, and technology factors whether they have a significant influence on credit demand. From this study, the results and conclusions of the service factor have a significant influence on credit demand. Factors other than service have an influence on credit demand but not significantly.